To Provide Higher Education Students with Basic Knowledge of Traditional Singing - Ahmedov Sharifjon Mamirdjanovich (International Journal on Integrated Education, 2021)
Shashmaqom is an invaluable masterpiece of Uzbek-Tajik music and has been the basis of the musical culture of these peoples since ancient times. Historical and theoretical information about maqoms is found in oriental written sources, mainly in musical treatises. Music has always played an important role in the life of our people. This is evidenced by the discovery of a bone flute 3,200 years ago in the village of Muminabad near Samarkand. In the article, the author provides recommendations for higher education students in the field of traditional singing.